A new target for treating intervertebral disk degeneration: gut microbes - Wang, Kaizhong; Liu, Xiangyan; Huang, Huagui; Suo, Moran; Wang, Jinzuo; Liu, Xin; Zhang, Jing; Chen, Xin; Li, Zhonghai (Frontiers in Microbiology, 2024)
Intervertebral disk degeneration (IDD) is a common clinical spinal disease and one of the main causes of low back pain (LBP). Generally speaking, IDD is considered a natural degenerative process with age. However, with the deepening of research, people have discovered that IDD is not only related to age, but also has many factors that can induce and accelerate its progression. In addition, the pathogenesis of IDD remains unclear, resulting in limited traditional treatment methods that cannot effectively prevent and treat IDD. Conservative treatment may lead to patients’ dependence on drugs, and the pain relief effect is not obvious. Similarly, surgical treatment is highly invasive, with a longer recovery time and a higher recurrence rate. With the deepening of exploration, people have discovered that intestinal microorganisms are an important symbiotic microbial community in the human body and are closely related to the occurrence and development of various diseases. Changes in intestinal microorganisms and their metabolites may affect the body’s inflammatory response, immune regulation, and metabolic processes, thereby affecting the health of the intervertebral disk. In this context, the gut microbiota has received considerable attention as a potential target for delaying or treating IDD. This article first introduces the impact of gut microbes on common distal organs, and then focuses on three potential mechanisms by which gut microbes and their metabolites influence IDD. Finally, we also summarized the methods of delaying or treating IDD by interfering with intestinal microorganisms and their metabolites. Further understanding of the potential mechanisms between intestinal microorganisms and IDD will help to formulate reasonable IDD treatment strategies to achieve ideal therapeutic effects.